Environmental Awareness Education through Proverbs in Brunei Darussalam - Alas, Yabit (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: The aim of this study is to provide educators with a different perspective on the teaching and value of proverbs. In addition to the semantics and pragmatics of proverbs, the lateral words and phrases used are equally important and interesting for students living in a modern era and culture. Pupils, as early as the third grade in elementary school, can be introduced to proverbs with this method. So, this paper focuses on environmental education using Malay proverbs in schools. The local wisdom of proverbs reflects views from earlier times, defining the culture, and its values. I try to explore how traditional Malay people coexisted with nature. Using observations of their surroundings, they crafted proverbs using beautiful phrases and conveyed wise messages. The educators can use this wisdom in teaching about the relationship between plants, animals, and natural objects; and how to mitigate or prevent natural calamities. The paper describes proverbs with an environmental theme and introduces the concept of environmental awareness education integrated with teachings from the Malay language. Due to the time depth and language dynamic, the words or phrases used in proverbs might change over time, which poses challenge to learners. It is important for teachers to apply an integrated learning approach in the teaching of proverbs. Besides the meaning of the proverbs, students should first understand the words or the phrases that built the proverbs and appreciate our forefathersâ ingenuity, especially its relations with the environment.KEY WORD: Proverbs; Malay Language; Environment; Education; Integrated Learning.Â RESUME: âPendidikan Kesedaran Alam Sekitar melalui Peribahasa di Negara Brunei Darussalamâ. Tujuan kajian ini adalah untuk memberi pendidik dengan perspektif yang berbeza mengenai pengajaran dan nilai peribahasa. Sebagai tambahan kepada semantik dan pragmatik peribahasa, perkataan dan frasa yang digunakan adalah sama penting dan menarik untuk pelajar yang tinggal di era dan budaya moden. Murid, seawal darjah Â ketiga di sekolah rendah, boleh diperkenalkan kepada peribahasa dengan kaedah ini. Oleh itu, makalah ini memberi tumpuan kepada pendidikan alam sekitar dengan menggunakan peribahasa Melayu di sekolah. Kebijaksanaan tempatan peribahasa mencerminkan pandangan dari zaman dahulu, menentukan budaya, dan nilai-nilainya. Saya cuba untuk meneroka bagaimana orang-orang Melayu tradisional bersubahat dengan alam semula jadi. Menggunakan pemerhatian persekitaran, mereka menghasilkan peribahasa dengan frasa yang indah dan menyampaikan mesej bijak. Para pendidik boleh menggunakan kebijaksanaan ini dalam mengajar tentang hubungan antara tumbuhan, haiwan, dan objek semula jadi; serta bagaimana untuk mengurangkan atau mencegah bencana alam. Makalah ini menerangkan peribahasa dengan tema alam sekitar dan memperkenalkan konsep pendidikan kesedaran alam sekitar yang bersepadu dengan pengajaran bahasa Melayu. Oleh kerana kedalaman waktu dan bahasa yang dinamik, perkataan atau frasa yang digunakan dalam peribahasa mungkin berubah dari semasa ke semasa, yang menimbulkan cabaran kepada pelajar. Adalah penting bagi guru untuk menggunakan pendekatan pembelajaran bersepadu dalam mengajar peribahasa. Selain makna peribahasa, pelajar harus terlebih dahulu memahami kata-kata atau frasa yang membina peribahasa dan menghargai kepintaran leluhur kita, terutama dalam hubungkaitnya dengan persekitaran.KATA KUNCI: Peribahasa; Bahasa Melayu; Persekitaran; Pendidikan; Pembelajaran Bersepadu.About the Author: Dr. Yabit Alas is a Lecturer at the Faculty of Arts and Social Sciences UBD (University of Brunei Darussalam), Jalan Tungku Link, BE1410, Negara Brunei Darussalam. For academic interests, the author is able to be contacted via e-mail address at: yabit.alas@ubd.edu.bnSuggested Citation: Alas, Yabit. (2017). âEnvironmental Awareness Education through Proverbs in Brunei Darussalamâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Volume 10(2), November, pp.139-150. Bandung, Indonesia: Minda Masagi Press and UNIPA Surabaya, ISSN 1979-0112. Article Timeline: Accepted (January 15, 2017); Revised (July 13, 2017); and Published (November 30, 2017).